Youth beyond borders: Methodological challenges in youth information interaction. Issue 1 (2014) - Waugh, Amanda; Ahn, June; Magee, Rachel M.; Bowler, Leanne; Agosto, Denise E.; Subramaniam, Mega
ABSTRACT: The pace of technological change is rapid and the impact of this acceleration on the information behavior of youth from diverse backgrounds is multifaceted. Most young people have online access in some form, but the uses and quality of access vary tremendously (Madden, Lenhart, Duggan, Cortesi & Gasser, 2013). With the growth and variation of information behaviors among youth in social media and the mobile Web, keeping pace with research methods used to capture these behaviors and phenomena continues to be a discussion among scholars. Adding to the complications of research in this area, youth are increasingly using information and communications technologies (ICT) across platforms for a variety of information behaviors, including academic and social reasons (Agosto & Abbas, 2010 ). It is often not enough to solely examine a young person's Twitter feed ‐ we need to see how that conversation carries from Twitter, to direct messages, to texting, to a Facebook post and so on. This variation suggests a need for greater nuance in research (Madden, Lenhart, Duggan, Cortesi & Gasser, 2013; Gasser, Cortesi, Malik & Lee, 2012). This panel will bring together several researchers experienced in studying youth information practices to discuss their methodologies and strategies in dealing with these intricate issues. This panel will be conducted in a roundtable style – encouraging deep conversation between the researchers and the audience. This will be followed by a small group discussions with the audience and conclude by sharing back best practices uncovered through the group discussions. Through attending this panel, attendees will engage with current developments in diverse youth, ICT and research methodologies, and identify priorities and approaches for future work in these areas.